Treatment Measurement of Left-Right Foot Sensitivity Before and After Doing Marble Media Foot Exercises - Windartik, Emyk (Jurnal Kesehatan Pasak Bumi Kalimantan, 2025)
Management of diabetes mellitus disease, one of which is a physical activity aimed at preventing diabetic wounds, namely by foot exercise activities. Foot exercise is done using marbles to increase foot sensitivity. The purpose of the study was to analyze the measurement of left-right foot sensitivity before and after doing foot exercises using marbles. The type of research used was an experimental one-group pre-post-test design. The population of all Type 2 Diabetes Mellitus sufferers was taken using a purposive sampling technique of 65 participants. The research instrument was Standard Operating Procedures for learning foot gymnastics and observation sheets for assessing foot sensitivity with a monofilament test. Data analysis used the Paired t-test. The results of measuring the sensitivity of the right foot before and after being given foot exercises using marbles were at an average of 5.17 changing to 8.17. While the left foot measurement averaged 5.03 changing to 8.02. The results of the statistical test using the paired t-test obtained a p-value of 0.001